Improved Retention of Chest Compression Psychomotor Skills With Brief "Rolling Refresher" Training. Issue 4 (August 2017) - Niles, Dana E.; Nishisaki, Akira; Sutton, Robert M.; Elci, Okan U.; Meaney, Peter A.; O'Connor, Kathleen A.; Leffelman, Jessica; Kramer-Johansen, Jo; Berg, Robert A.; Nadkarni, Vinay
Abstract : Introduction: High-quality cardiopulmonary resuscitation (CPR) is critical to improve survival from cardiac arrest. However, cardiopulmonary resuscitation knowledge and psychomotor skill proficiency are transient. We hypothesized that brief, in situ refresher training will improve chest compression (CC) psychomotor skill retention for bedside providers. Methods: Nurses completed a baseline skill evaluation of CC quality 6 months after traditional basic life support recertification. Data collected using ResusciAnne with SkillReporter included the following: CC depth, rate, complete release, and correct hand position. Total compliance was defined as 100% CC with depth of 50 mm or greater, rate of 100/min or greater, and more than 90% complete release. After the baseline evaluation, the subjects completed "Rolling Refresher" (RR) CC psychomotor training using audiovisual feedback every 2 to 3 months for 12 months until 30 seconds of CCs fulfilling total compliance criteria was achieved. Chest compression quality evaluations were repeated twice ("RR 6 month" and "RR 12 month" evaluation) after implementation of RR program. Results: Thirty-seven providers enrolled and completed the baseline evaluation. Mean depth was 36.3 (9.7) mm, and 8% met criteria for depth, 35% for rate, and 5% for total compliance. After RRs were implemented, CC quality improved significantly at RR 6-month evaluation: odds ratio for meeting criteria were the following: depth of 35.1 (95% confidence interval = 2.5496, P = 0.009) and total compliance of 22.3 (95% confidence interval = 2.1239, P = 0.010). There was no difference in CC quality at RR 12-month versus RR 6-month evaluation. Conclusions: Retention of CC psychomotor skill quality is limited to 6 months after traditional basic life support recertification. Rolling Refresher CC training can significantly improve retention of CC psychomotor skills. Whether CC skills are improved, maintained, or deteriorate after 12 months of Refresher training and optimal frequency of Refreshers is unknown.